The Effect of Role Play and Audio-Visual Interventions Based on Local Wisdom in Enhancing Disaster Preparedness Behavior among Elementary Schoolchildren - Ni Luh Seri Astuti; Triyana Puspa Dewi; I Made Moh. Yanuar Saifudin; I Gusti Kadek Agus Dwi Putra; Ni Kadek Juni Antari (Babali Nursing Research, 2023)
Introduction: Disaster-prone regions like Karangasem Regency, located in the Ring of Fire, are susceptible to earthquakes and volcanic eruptions. It becomes imperative to ensure that students possess adequate disaster preparedness knowledge and skills. The objective of this study was to evaluate the efficacy of role-playing and audio-visual educational interventions based on local wisdom in improving disaster preparedness behavior among elementary school students.Methods: This study employed a quasi-experimental design using a pre- and post-test approach, including a control group. The study participants consisted of elementary school students in grades 4, 5, and 6 who were willing to participate and physically fit. A total of 56 students were included in the study, selected through simple random sampling, with 28 students assigned to each of the intervention and control groups. The research was conducted at SD 6 Ban, situated in Kubu, Karangasem, Bali.Results: The utilization of audiovisual educational videos and locally rooted role-playing activities significantly enhanced disaster preparedness behavior among elementary school students at SD 6 Ban. This effectiveness was demonstrated by the p-values, which were 0.001, 0.002, and 0.001 for knowledge, attitude, and behavior, respectively, indicating a substantial positive impact of the intervention on all three aspects.Conclusion: The audiovisual educational videos and locally rooted role-playing activities have proven to be effective in enhancing the elements of knowledge, attitude, and behavior among elementary school students. It is our hope that this method can be consistently applied as an ongoing intervention to further improve disaster preparedness among students. Keywords: Audiovisual, disaster preparedness, local wisdom, role play, schoolchildren